SERUM OESTRADIOL -17â AND PROGESTERONE PROFILE IN HAMPSHIRE GILTS FOLLOWING SYNCHRONIZATION OF OESTRUS BY PGF 2∝ ANALOGUES (Indian Journal of Animal Production and Management, 2015)
Following synchronization of oestrus by PGF2-∝ analogue, serum oestradiol-17â and progesterone concentration during different stages of gestation were carried out in a total 18 pubertal Hampshire gilts reared in the Base Pig Breeding Farm, Department of Animal Husbandry and Veterinary, Government of Assam, Khanapara,Guwahati. The pubertal gilts were divided in to three groups viz. Group I and II as treated and Group III as control. Gilts of Group I received 5ml Iliren during luteal phase of cycle whereas gilts of Group II received Serum oestradiol -17â and progesterone profile in Hampshire gilts two injection of 5ml Iliren at 11 days apart. The mean serum oestradiol-17â and progesterone showed significantly (P
Keywords: Oestradiol-17â; Progesterone; PGF2-∝ analogue; Gestation; Synchronization